Are antibiotics effective in acute flares of chronic asthma?. Issue 9 (September 2015) - Carroll, Katherine H.; Grogan, Scott P.
Abstract : Evidence‐Based Answer : In patients with acute asthma flares, at least 3 weeks of macrolide therapy added to standard asthma care may be associated with improved symptom control (SOR: B, meta‐analysis of RCTs). There does not appear to be any benefit with amoxicillin (SOR: B, meta‐analysis) or macrolide therapy for 16 weeks (SOR: B, RCTs).